Experimental Study and Analysis of Drilling Process on Aluminium-Tin Multi Material - Naveen Kumar; Lokesh Singh (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
The latest generation multi-material drilling processes for aluminum-tin mixture have garnered attention due to their application in advanced manufacturing and structural applications. This paper explores the recent advancements in drilling techniques tailored specifically for aluminum-tin alloys, which are characterized by their lightweight properties and enhanced mechanical strength. Key aspects such as tooling strategies, machining parameters optimization and surface integrity enhancement are discussed in detail. Moreover, the paper synthesized current research findings on the challenges associated with drilling aluminum-tin compounds, including tool wear, heat generation and burr formation. Strategies for mitigating these challenges through novel tool materials, advanced cooling techniques and innovative process control methods are also highlighted. By consolidating the latest research outcomes, this review aims to provide a comprehensive understanding of the state-of-the-art in multi-material drilling of Aluminum-tin plates, offering insights into future research directions and industrial applications in aerospace, automotive and other high performance sectors.
Keywords: Multi Material; Drilling Process; Drill Bits; Aluminum-Tin; Casting; Molding